Work-based Learning – Challenge for Competitive Vocational Education Experience of Latvia - Brante, Ilze; Sloka, Biruta (Beijing Union University and Success Culture Press, 2021)
Work-based learning is implemented in Latvia and there are many aspects to be investigated as work-based learning require several stakeholder mutual co-operation by vocational education institutions, by teaching staff at vocational education institutions, companies, as well as different employers’ organisations in the situation of demographic changes by reducing of numbers of young people. Aim of research – investigate different approaches in realisation of work-based learning in seeking innovative approaches and findings in countries with bigger experience in realisation of this kind of vocational education. Research methods applied: analysis of experience and findings reflected in scientific publications, analysis of statistical data on vocational education development in Latvia and analysis of practical development of work-based learning at Ogre Technical School.
Keywords: Work-based learning; vocational education; employer; student; praxis; service; innovations; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education